Availability and Placement of Electronic Nicotine Delivery Systems at the Point-of-Sale. Issue 8 (9th September 2017) - Wagoner, Kimberly G; Song, Eunyoung Y; King, Jessica L; Egan, Kathleen L; Debinski, Beata; Wolfson, Mark; Spangler, John; Sutfin, Erin L
Abstract: Introduction: Electronic nicotine delivery systems (ENDS) are widely available and come in a variety of forms, including disposable cigalikes and refillable tank systems. However, little is known about their placement at the point-of-sale. We explored the placement of various ENDS types among tobacco retailers. Methods: Systematic assessments at the point-of-sale were completed by trained data collectors in 90 tobacco retailers, including grocery stores, convenience stores, and pharmacies in North Carolina, United States. Availability and placement of various ENDS types including cigalikes, e-hookahs, tank systems, and e-liquids was recorded. Results: Almost all retailers (97.8%) sold cigalikes; 41.4% sold devices labeled as e-hookahs; 54.4% sold tank systems; and 56.2% sold e-liquids. Fewer than half of stores placed ENDS exclusively behind the counter; significant differences in ENDS placement were found by store type. Grocery stores carried cigalikes, tank systems, and e-liquids and placed them exclusively behind the counter. Pharmacies only sold cigalikes; most placed them exclusively behind the counter (91.7%) with cessation aids and other tobacco products. Convenience stores carried all ENDS types and placed them with other tobacco products (55.1%) and candy (17.4%). Only about one-third of convenience stores placed ENDS exclusively behind the counter. Conclusions: This exploratory study shows ENDS availability and placement at the point-of-sale varies by retailer type. Pharmacies placed cigalikes with cessation aids behind the counter suggesting their ability to aid in smoking cessation. Most convenience stores placed ENDS in self-service locations, making them easily accessible to youth. Findings highlight the need for ENDS regulation at the point-of-sale. Implications: Our study highlights the need for regulatory efforts aimed at ENDS placement at the point-of-sale. While pharmacies and grocery stores offered fewer ENDS types and typically placed them in clerk-assisted locations, all ENDS types were found at convenience stores, some of which were placed in youth-friendly locations. Regulatory efforts to control ENDS placement and limit youth exposure should be examined, such as requiring products be placed in clerk-assisted locations and banning ENDS placement next to candy.